2016
DOI: 10.1016/j.virol.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic and mutational analysis of ophiovirus movement proteins, belonging to the 30K superfamily

Abstract: Ophioviridae is a family of segmented, negative-sense, single-stranded RNA plant viruses. We showed that their cell-to-cell movement protein (MP) is an isolated member of the 30K MP superfamily with a unique structural organization. All 30K MPs share a core domain that contains a nearly-invariant signature aspartate. We examined its role in the MP of Citrus psorosis virus (CPsV) and Mirafiori lettuce big-vein virus (MiLBVV). Alanine substitution of this aspartate prevented plasmodesmata accumulation of MP(MiLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…S4, see Supporting Information). Interestingly, the MPs of several ophioviruses, including CPsV, have been shown recently to belong to the 30K superfamily (Borniego et al , ; Mushegian and Elena, ). In addition, ML phylogenetic analyses with the MP of representative nsRNA viruses infecting plants showed that CCGaV p46 is clustered together with the MPs of ophioviruses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4, see Supporting Information). Interestingly, the MPs of several ophioviruses, including CPsV, have been shown recently to belong to the 30K superfamily (Borniego et al , ; Mushegian and Elena, ). In addition, ML phylogenetic analyses with the MP of representative nsRNA viruses infecting plants showed that CCGaV p46 is clustered together with the MPs of ophioviruses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4Bii and iii). The identified region in MP CPsV contains an aspartic residue (D), which is also the first amino acid of an amino acid triad that is strictly conserved among ophiovirus MPs (45). This finding suggests that MP CPsV and other ophiovirus MPs have an autocatalytic protein cleavage activity.…”
Section: Resultsmentioning
confidence: 91%
“…Given that MP CPsV :GFP, but not GFP:MP CPsV , is capable of forming tubules at PD, we wondered whether this has functional relevance in virus movement. Since an infectious cDNA clone of CPsV to test this hypothesis by a reverse genetic approach is not available, we used an alternative assay to evaluate this activity (45,46). In this assay, we analyzed the capacities of MP CPsV :GFP and GFP:MP CPsV to trans-complement TMVΔMPΔCP-GFP, a previously reported movement-deficient TMV derivative (45).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations